Ganetespib radiosensitization for liver cancer therapy. Issue 4 (2nd April 2016) - Chettiar, Sivarajan T.; Malek, Reem; Annadanam, Anvesh; Nugent, Katriana M.; Kato, Yoshinori; Wang, Hailun; Cades, Jessica A.; Taparra, Kekoa; Belcaid, Zineb; Ballew, Matthew; Manmiller, Sarah; Proia, David; et al.
ABSTRACT: Therapies for liver cancer particularly those including radiation are still inadequate. Inhibiting the stress response machinery is an appealing anti-cancer and radiosensitizing therapeutic strategy. Heat-shock-protein-90 (HSP90) is a molecular chaperone that is a prominent effector of the stress response machinery and is overexpressed in liver cancer cells. HSP90 client proteins include critical components of pathways implicated in liver cancer cell survival and radioresistance. The effects of a novel non-geldanamycin HSP90 inhibitor, ganetespib, combined with radiation were examined on 3 liver cancer cell lines, Hep3b, HepG2 and HUH7, using in vitro assays for clonogenic survival, apoptosis, cell cycle distribution, γH2AX foci kinetics and client protein expression in pathways important for liver cancer survival and radioresistance. We then evaluated tumor growth delay and effects of the combined ganetespib-radiation treatment on tumor cell proliferation in a HepG2 hind-flank tumor graft model. Nanomolar levels of ganetespib alone exhibited liver cancer cell anti-cancer activity in vitro as shown by decreased clonogenic survival that was associated with increased apoptotic cell death, prominent G2-M arrest and marked changes in PI3K/AKT/mTOR and RAS/MAPK client protein activity. Ganetespib caused a supra-additive radiosensitization in all liver cancer cell lines at low nanomolar doses with enhancement ratios between 1.33–1.78. These results were confirmed in vivo, where the ganetespib-radiation combination therapy produced supra-additive tumor growth delay compared with either therapy by itself in HepG2 tumor grafts. Our data suggest that combined ganetespib-radiation therapy exhibits promising activity against liver cancer cells, which should be investigated in clinical studies.